Can we create a valid treatment algorithm for patients with drug resistant overactive bladder (OAB) syndrome or detrusor overactivity (DO)? Results from a think tank (ICI‐RS 2015). Issue 4 (April 2017) - Apostolidis, Apostolos; Averbeck, Marcio Augusto; Sahai, Arun; Rahmana'i, Sajjad; Anding, Ralf; Robinson, Dudley; Gravas, Stavros; Dmochowski, Roger
Abstract : Aims: To review and assess the definitions of drug resistance and the evidence supporting treatment for drug resistant overactive bladder/detrusor overactivity (OAB/DO). Methods: Evidence review of the extant literature and consensus of opinion was used to derive the summary recommendations. Results: Drug resistance or drug refractory status has been inconsistently defined and reported in current evident sources. Recent publications use some correlation of lack of efficacy and or experienced side effects to define drug resistance. Algorithms based upon these definitions largely relate to the appropriate use of neuromodulation or botulinum neurotoxin, based upon patient selection and patient choice. Current treatment pathways are hampered by inability to consistently profile patients to optimize management, particularly after failure of initial pragmatic treatment. Conclusions: Further research is recommended to better identify patient phenotype for purposes of directing optimized therapy for OAB/DO. Current treatment algorithms are influenced by extensive data generated from recent neuromodulation and botulinum neurotoxin trials.